Indywidualne uzgadnianie właściwości towaru w przypadku sprzedaży konsumenckiej - Koszowski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The Polish Consumer Sale Act distinguishes instances in which arrangements between parties as to the quality of aconsumer good are made from the instances in which such arrangements do not occur. Depending on each of these two situations, there are envisaged different presumptions of the conformity of a good with the contract. This division can be, however, very misleading insofar as it suggests that, in the instances in which individual agreements on the quality of a good occur, the presumption provided for the instances in which such agreements are not present does not work. Conversely, if they are only at stake, the premises of that presumption must always be fulfilled so that one can presume that a given good conforms to the contract. The only exception is here the actual or presumed knowledge of the non-conformity of a given good with the contract on the part of the buyer.According to the provisions of the Polish Consumer Sale Act, as a result of individual arrange-ments, we presume the state of the conformity with the contract if a good delivered to the buyer: a complies with thedescription of this good given by the seller, b posseses the qualities of samples or models of this good which have been shown to the buyer, and c fits for any particular purpose about which the consumer has notified the seller within the act of concluding acontract upon which he/she has bought this good. Moreover, quality of consumer goods must meet standards on which parties have expressly agreed, especially by the adoption of special contractual clauses in that matter. Namely, except parties do decide otherwise, only sucha good can be deemed to be in conformity with the contract. The same remark concerns agreements made per facta concludentia, i.e. agree-ments that we assume to be reached due to indicative behaviors of the parties involved.
Keywords: sprzedaż konsumencka; właściwość towaru